The effect of different structural decoration geometries on vibration propagation in spider orb webs - Greco, G.; Dal Poggetto, V. F.; Lenzini, L.; Castellucci, F.; Pugno, N. M. (PLOS ONE, 2025)
The stabilimentum, or structural decoration, in spider orb webs is a fascinating structure. While the species that construct stabilimenta and their building techniques are well-documented, the precise functions of these structures remain unclear. This knowledge gap arises from conflicting reports in the literature and the significant behavioral flexibility spiders exhibit when incorporating stabilimenta into their webs. Notably, spiders can build stabilimenta in various geometries, which may influence the dynamical properties of orb webs—a relationship that has yet to be quantitatively explored. In this study, we combined extensive field observations with computational simulations to address this gap. The fieldwork focused on documenting the range of stabilimentum geometries in Argiope bruennichi, while the simulations examined how these variations influence the propagation of elastic waves across the web. Our results suggest that the stabilimentum, acting as an additional inertial mass, does not significantly slow down the propagation of elastic waves generated by prey impact in the transverse and normal directions relative to the radial threads. However, when prey impact induces vibrations tangential to the spiral threads of the web, the presence of the stabilimentum enhances the spider’s ability to detect prey location by allowing vibrations to reach a greater number of output points compared to webs without a stabilimentum. These findings deepen our understanding of the mechanical role of stabilimenta and provide new insights for the development of bio-inspired metamaterials, particularly those with tunable dynamic elastic properties.